Removal of reactive dyes from aqueous solutions by a non-conventional and low cost agricultural waste: adsorption on ash of Aloe Vera plant - Mohammad Malakootian; Hossein Jafari Mansoorian; Ahmad Reza Yari (Iranian Journal of Health, Safety and Environment, 2014)
Dyes are an important class of pollutants and disposal of them in precious water resources must be avoided. Among various methods adsorption occupies a prominent place in dye removal. The aim of this study is to evaluate adsorption of dye Reactive Red 198 and Blue 19 (RR-198 & RB-19 (on to Aloe Vera plant ash from aqueous solutions. In this research Aloe Vera ash was prepared at laboratory conditions and then after shredding, screened by ASTM standard sieve with 60 -200 mesh sizes and the effects of pH (3-12), adsorbent dose (0.1-1 g/L), contact time (10-60 min), initial dye concentration (10-160 mg/L) and temperature were investigated in the experiment. In different samples Dye concentration was measured by spectrophotometer at 592 nm and 520 nm wavelength for RR198 and RB19 respectively. Also the Langmuir and Freundlich adsorption isotherms were determined in order to describe the relations between the colored solutions and the adsorbent. The results of this study showed that acidic conditions were more conducive to enhance the hydrolysis rate than basic ones as the decomposition was optimum at pH 3. The adsorption rate of RR-198 and RB-19 dyes was increased by increasing of initial dye concentration, increasing of adsorbent dose in 0.1 to 0.4 mg/L. Dye solution was decolorized in a relatively short time (20 min). The efficiencies for RR-198 and RB- 19 reactive dyes were 82.68% and 90.42% respectively. The maximum adsorption capacity (qmax) has been found to be 80.152 mg/g for RR-198 reactive dye and 88.452 mg/g for Blue 19 reactive dye. Adsorption isotherms were examined by Freundlich and Langmuir isotherm that finally showed the Freundlich multilayer isotherm has better accordance with dates. The results indicate that Aloe Vera ash plant as a natural and inexpensive adsorbent is a suitable adsorbent for the adsorption of textile dyes.